(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Some reflections are given about the inscription dedicated to dea Degant. (CIL II 5672), discovered in Cacabelos (León) at the end of the 19th century. From the epigraphical analysis, this paper focuses on the relations with other religious dedications from the Roman Empire that includes in honorem formula. If our hypothesis is correct, the goddess Deganta would be the protective divinity of the cognatio Argael(orum), as the Lares Lubancos are the protectors of the Douilinic(orum) horum mentioned in an inscription from Conimbriga.